2018
DOI: 10.1101/470419
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The Toll pathway inhibits tissue growth and regulates cell fitness in an infection-dependent manner

Abstract: The Toll pathway regulates the cellular response to infection via the transcriptional upregulation of antimicrobial peptides. Apart from its role in innate immunity, this pathway has also been reported to be important for the elimination of loser cells in a process referred to as cell competition, which can be locally triggered by secreted factors released from winner cells. In this work we provide evidence that the inhibition of Toll signaling not only increases the fitness of loser cells, but also bestows a … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…While results presented here may appear reminiscent of Toll-mediated cell competition, we do notice an important distinction: namely, that local interactions of cell neighbors—as in localized Toll-mediated tissue surveillance (Alpar et al, 2018; Meyer et al, 2014)—may not suffice for tumor elimination, particularly when the latter displays sufficient growth. Instead, the paradigm of host Toll signaling-dependent tumor remission shown here appears comparable with Toll-mediated tissue surveillance by microbial infection in Drosophila (Germani et al, 2018), or tumor remission induced by Coley’s toxins (Coley) or by TLR agonists (Michaelis et al, 2019).…”
Section: Main Textmentioning
confidence: 84%
See 2 more Smart Citations
“…While results presented here may appear reminiscent of Toll-mediated cell competition, we do notice an important distinction: namely, that local interactions of cell neighbors—as in localized Toll-mediated tissue surveillance (Alpar et al, 2018; Meyer et al, 2014)—may not suffice for tumor elimination, particularly when the latter displays sufficient growth. Instead, the paradigm of host Toll signaling-dependent tumor remission shown here appears comparable with Toll-mediated tissue surveillance by microbial infection in Drosophila (Germani et al, 2018), or tumor remission induced by Coley’s toxins (Coley) or by TLR agonists (Michaelis et al, 2019).…”
Section: Main Textmentioning
confidence: 84%
“…Fly stocks were grown on standard axenic corn meal-agar medium supplemented with streptomycin (400μg/ml) along with anti-fungal Antimycotic Nipagin (0.15 g per 100 ml), at 25 °C including those involving Gal4 driver lines and instances of shift to 18± 1°C at 4.5 dAEL (days A fter E gg L aying) are mentioned wherever done. Care has taken to raise larvae and flies under aseptic and uncrowded conditions, especially when assaying for systemic immune responses (also, see Germani et al, 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Double knockdown of Atg1 and fwe or azot was not additive, suggesting that they act in a linear pathway, but this was not further explored. Similarly, innate immune signaling has been implicated in elimination of both Myc low and Rpl14E/+ loser cells (Meyer et al, 2014;Germani et al, 2018). Inhibition of innate immune signaling, specifically in Hel25E À/À loser cells, also counteracted cell elimination.…”
mentioning
confidence: 99%
“…They found that during Myc-induced and Minute-induced CC, Toll-related receptors (TRR) are more expressed in loser cells and they are activated by the ligand Spätzle, leading to NF-κβ activation and apoptosis in Drosophila wing disc (Alpar et al, 2018;Meyer et al, 2014). In a later study (Germani et al, 2018), this type of TRR-mediated competition was found to depend on the septic status of flies, indicating that a systemic response to infection is required for TRR-mediated cell competition.…”
Section: Innate Immunitymentioning
confidence: 96%